Promoting the inclusion of families through the development of Work Projects. A case study - Ruiz Torres, María del Carmen; Mérida Serrano, Rosario (Revista Complutense de Educación, 2015)
This is a qualitative research focused on a case study in a classroom of 5-years-old children. The potential of the Work Projects (hereinafter PT) methodology is analysed to facilitate the inclusion of families in the teaching-learning process of their children. Through three detailed interviews to the families and pedagogical documentation, we obtain information which -after the analysis- reveals the following findings: (1) PT methodology uses as an essential part of the teaching-learning process the knowledge and professional experience of families; (2) Families assume a role of tutoring and support in the educational process of their children, which occur simultaneously at school and at home. They adjust their actions to the demands and carry out the task of mediating between children’s skills and learning new material; (3) The collaboration of families, present from the beginning to the end of the PT, requires a very high commitment, proving to be an indispensable element for the development of this methodology; and (4) Families identify listening to students as a strength of the PT. As limitations, the excessive time required, the differences which can generate in students the different levels of involvement of their families and the discontinuity of this method with more traditional ways of dealing with teaching at later stages.